PEER TO PEER EMPOWERMENT: HOW PEER EDUCATION AFFECTS TEEN ATTITUDES TOWARD PREVENTING UNWANTED PREGNANCY - Nur Maziyah Hurin'in; Tri Yunita Fitria Damayanti; Nur Cholila (Universitas Airlangga, 2026)
Introduction: Cases of juvenile delinquency in the era of the Industrial Revolution 4.0 are increasingly prevalent and attracting attention. Adolescent sexual behavior poses various risks, including sexually transmitted diseases (STDs), unwanted pregnancies (UP), abortion, school dropout, and moral issues among adolescents. This study aims to analyze the effect of peer education on adolescents’ attitudes toward preventing unwanted pregnancy. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The population consisted of 89 ninth-grade female students in a junior high school. The sample sizewas determined using the Lemeshow formula, resulting in 70 participants selected through simple random sampling. The independent variable was pregnancy prevention education. Data were analyzed using the Wilcoxon test with the assistance of SPSS software. Results: At a significance level of α = 0.05, the result of Asymp. Sig. (2-tailed) = 0.000 (< 0.05) indicates a significant effect of peer group health education on adolescents’ attitudes toward preventing unwanted pregnancy. Conclusions: Peer health education significantly influences adolescents’ positive attitudes toward preventing unwanted pregnancy. Future research is recommended to develop digital-based educational methods and explore the integration of artificial intelligence.